Analisis Perbandingan Metode Logika Fuzzy Untuk Menentukan Harga Penjualan/Pembelian Sepeda Motor - Egi Sundawa; Mega Nur Utami; Angga Syaf Putra; Malik Ibrahim Nur; Perani Rosyani (BISIK : Jurnal Ilmu Komputer, Hukum, Kesehatan dan Sosial Humaniora, 2022)
Increase the purchase of new motorcycles, also increase the level of sales of used motorcycles. Because most people will sell a motorcycle first, then buy a new motorcycle with more sophisticated specifications. Only the sale and purchase of used motorcycles is still used where the results are not in accordance with the expected specifications. For that we need a system that can determine the selling price accurately. The selling price can use comparisons from several journals and use the Fuzzy Infrence System (FIS) method Fuzzy Sugeno and Fuzzy Tuskamoto, it is hoped that it will make it easier for buyers/motorcycle sellers to determine the selling price of used motorbikes more accurately according to the condition of the motorbikes to be sold. or bought. In comparison of prices and specifications of motorcycles that will be bought or sold, the Mamdani methodhas.